2011
DOI: 10.1016/j.jecp.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s haptic exploratory procedures

Abstract: Adults vary their haptic exploratory behavior reliably with variation both in the sensory input and in the task goals. Little is known about the development of these connections between perceptual goals and exploratory behaviors. Thirty-six children 3, 4, and 5 years of age and 20 adults completed a haptic intra-modal match-to-sample task. Participants were instructed to feel the shape, texture, rigidity, or weight of a sample object, and then asked to find which of three test objects matched the sample on tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 21 publications
3
22
2
1
Order By: Relevance
“…The finding that children are able to execute the same EPs as adults is in line with the results of Kalagher and Jones (2011), who concluded that children produced adult-like EPs and matched the sample objects correctly to the standard on the different dimensions. Moreover, we found that both children and adults used some additional EPs, sometimes alone and sometimes in combination with the dominant EP.…”
Section: Exploratory Behavior Of Children and Adultssupporting
confidence: 87%
See 1 more Smart Citation
“…The finding that children are able to execute the same EPs as adults is in line with the results of Kalagher and Jones (2011), who concluded that children produced adult-like EPs and matched the sample objects correctly to the standard on the different dimensions. Moreover, we found that both children and adults used some additional EPs, sometimes alone and sometimes in combination with the dominant EP.…”
Section: Exploratory Behavior Of Children and Adultssupporting
confidence: 87%
“…According to Bushnell and Boudreau, the onset of all EPs is thus in the first year of life. Kalagher and Jones (2011) recently assessed 36 sighted children (3-5 years) and 20 adults with a haptic match-tosample task. The participants could not see their hands during the experiment.…”
Section: Manual Exploration In Sighted Childrenmentioning
confidence: 99%
“…There is a possibility that the left-lateralized bias found in the LOC in some studies (e.g., Kim, Stevenson, & James, 2012; Yalachkov et al, 2015) may be due not solely to the hand used to explore the stimulus, but also to the strong right-handed preference of the participants tested in these studies. Thus, to mitigate hand-in-use effects in the current study, haptic exploration was performed bimanually similar to other developmental studies of young children (Bushnell & Baxt, 1999; Kalagher & Jones, 2011a, 2011b). Additionally, to minimize differences in handedness preference, we recruited mostly right-handed participants, and did not include any strongly left-preferring participants.…”
Section: Discussionmentioning
confidence: 99%
“…It was decided based on several reasons that behavioral responses would not be recorded during the MRI scan. First, both children and adults show a reliable preference for two-handed haptic exploration of 3D objects, particularly with regard to shape recognition (Lederman & Klatzky, 1987; Kalagher & Jones, 2011a, 2011b). To include a button press response would restrict exploration to the unnatural single-handed mode, which would likely be more distracting for children than adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation